METHODOLOGICAL BASIS OF DEVELOPMENT OF WHOLESALE MARKETING LOGISTICS (Marketing Journal, 2025)
This article describes the content of the concept of marketing logistics, the relevance of developing marketing logistics in wholesale trade, the main parameters of marketing logistics as a result of the symbiosis of marketing and logistics in wholesale trade, and the main tasks of marketing and logistics in wholesale trade.
Keywords: marketing logistics; product assortment formation; product inventory; new sales markets; sales channels; freight transportation; product movement